2016
DOI: 10.1038/srep39146
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Adaptive Immunity: A New Role for PAFR Antagonists

Abstract: We have previously shown that the Platelet-Activating Factor Receptor (PAFR) engagement in murine macrophages and dendritic cells (DCs) promotes a tolerogenic phenotype reversed by PAFR-antagonists treatment in vitro. Here, we investigated whether a PAFR antagonist would modulate the immune response in vivo. Mice were subcutaneously injected with OVA or OVA with PAFR-antagonist WEB2170 on days 0 and 7. On day 14, OVA–specific IgG2a and IgG1 were measured in the serum. The presence of WEB2170 during immunizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…In previous studies, we described the effect of the PAFR blockage in DCs during maturation induced by LPS. A pretreatment with a PAFR antagonist reduced the IL-10 and PGE 2 secretion by DCs and increased their ability in promoting T cell proliferation and Th1-like adaptive response in vitro and in vivo [6,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we described the effect of the PAFR blockage in DCs during maturation induced by LPS. A pretreatment with a PAFR antagonist reduced the IL-10 and PGE 2 secretion by DCs and increased their ability in promoting T cell proliferation and Th1-like adaptive response in vitro and in vivo [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that mice that were immunized in the presence of a PAFR antagonist developed an enhanced antigen-specific adaptive immune response. We also observed that vaccination of mice with dendritic cells (DCs) that had been previously treated with PAFR antagonists and stimulated with lipopolysaccharide (LPS) also induced higher antigen-specific T cell proliferation, suggesting that the activation of this receptor in the site of immunization could adjust both innate and adaptive immunity responses [6].…”
Section: Introductionmentioning
confidence: 91%
“…The PAF/PAFR axis can also suppress the immune response by inducing tolerogenic dendritic cells 41 and proliferation of myeloid-derived suppressor cells 42 . In these cells, PAFR-mediated suppression involves IL10 and prostaglandin production 43 .…”
Section: Pafr and The Tumor Microenvironmentmentioning
confidence: 99%
“…Besides the well‐established pro‐inflammatory effects of PAF, in select cases, PAFr has also been implicated in damping the immune response, inducing immune suppression . Several in vitro and in vivo studies have reported that PAFr activation in macrophages and dendritic cells is able to shift these cells toward an anti‐inflammatory or tolerogenic phenotype . Thus, PAFr antagonists may have the ability to fine‐tune the innate and adaptive immunity with a potential role in immunization …”
Section: Inflammatory Diseasesmentioning
confidence: 99%